Q. 1 E4.1( 11 Votes )

# In the following,

Answer :

p + q = –5

⇒p = –5–q

putting the value of q in other equation,

⇒ pq = –6

⇒ (–5–q)q = –6

⇒–5q–q^{2} = –6

⇒q^{2} + 5q–6 = 0

⇒q^{2} + 6q–q–6 = 0

⇒q(q + 6)–1(q + 6) = 0

⇒ (q–1)(q + 6) = 0

so, q = 1 & q = –6

as p = –5–q

thus, p = –5–1 & p = –5 + 6

p = –6 & p = 1

Rate this question :

Factorise:

</pKarnataka Board - Mathematics Part I

Factorise:

</pKarnataka Board - Mathematics Part I

Factorise:

</pKarnataka Board - Mathematics Part I

In the following,Karnataka Board - Mathematics Part I

In the following,Karnataka Board - Mathematics Part I

In the following,Karnataka Board - Mathematics Part I

In the following,Karnataka Board - Mathematics Part I

Factorise:

</pKarnataka Board - Mathematics Part I

Factorise:

</pKarnataka Board - Mathematics Part I

Factorise:

</pKarnataka Board - Mathematics Part I